Bioelectricity production using a new electrode in a microbial fuel cell - Ozkaya, Bestamin; Akoglu, Busra; Karadag, Dogan; Aci, Gokcen; Taskan, Ergin; Hasar, Halil (SPRINGER, 2012)
Electrode materials play a key role in enhancing the electricity generation in the microbial fuel cell (MFC). In this study, a new material (Ti-TiO2) was used as an anode electrode and compared with a graphite electrode for electricity generation. Current densities were 476.6 and 31 mA/m(2) for Ti-TiO2 and graphite electrodes, respectively. The PCR-DGGE analysis of enriched microbial communities from estuary revealed that MFC reactors were dominated by Shewanella haliotis, Enterococcus sp., and Enterobacter sp. Bioelectrochemical kinetic works in the MFC with Ti-TiO2 electrode revealed that the parameters by non-linear curve fitting with the confidence bounds of 95% gave good fit with the kinetic constants of eta (difference between the anode potential and anode potential giving one-half of the maximum current density) = 0.35 V, K (s) (Half-saturation constant) = 2.93 mM and J (max) = 0.39 A/m(2) for T = 298 K and F = 96.485 C/mol-e(-). From the results observed, it is clear that Ti-TiO2 electrode is a promising candidate for electricity generation in MFC.
Keywords: MFC; Ti-TiO2 electrode; Kinetics; Microbial community; ELECTRICITY-GENERATION; BACTERIAL COMMUNITIES; ANODE; PERFORMANCE; DIOXIDE; Biotechnology & Applied Microbiology; Engineering